Transmitted drug‐resistance in human immunodeficiency virus‐infected adult population in El Salvador, Central America. (19th June 2013) - Holguín, Á.; Yebra, G.; Martín, L.; de, A. T.; Ruiz, L. E.; Quezada, A. Y.; Nieto, A. I.; Escobar, G.; Antonelli, G.
Abstract El Salvador harbours one of the largest Central American human immunodeficiency virus (HIV) epidemics, but few studies have analysed it in depth. Here, we describe the presence of transmitted drug resistance (TDR) and HIV variants in the HIV‐infected adult population in El Salvador. Dried blood spots from 119 HIV‐infected antiretroviral‐naive adults attended in El Salvador were collected in 2011. The TDR was assessed according to the list recommended by the WHO. HIV‐1 variants were described using phylogeny. Pol sequences could be amplified in 88 patients (50.6% men), with a mean age of 35 years. Almost all (96.7%) were infected with HIV through sexual practice and 58.7% were recently diagnosed. The mean CD4+ count was 474 cells/mm3 and 43.1% and 15.5% of patients showed moderate (<500 CD4 cells) or severe (<200) immune suppression, respectively. HIV‐1 viral load was >100 000 copies/mL in 24.7% of patients and <2000 copies/mL in 9.1%. Five samples (5.7%) harboured any TDR mutation: 2.3% for nucleoside reverse transcriptase inhibitor (NRTI) and non‐nucleoside reverse transcriptase inhibitor (NNRTI), and 1.4% for protease inhibitor (PI). All showed only one TDR single‐class resistance mutation: M184I (two cases) for NRTI, K101E and K103N for NNRTI and L23I for PI. All viruses excepting one (URF_BG) belonged to subtype B. No phylogenetic TDR networks were found. In conclusion, we report a TDR prevalence of 5.7% in El Salvador, lower than in other Central American studies. Periodical studies are essential to monitor and prevent TDR emergence in low‐income and middle‐income regions. Also, more efforts are needed to promote early diagnosis and prevention of infection in El Salvador.